UV-Light-Tunable p-/n-Type Chemiresistive Gas Sensors Based on Quasi-1D TiS3 Nanoribbons: Detection of Isopropanol at ppm Concentrations - Victor V. Sysoev; Andrey V. Lashkov; Alexey Lipatov; Ilya A. Plugin; Michael Bruns; Dirk Fuchs; Alexey S. Varezhnikov; Mustahsin Adib; Martin Sommer; Alexander Sinitskii (Sensors, 2022)
The growing demand of society for gas sensors for energy-efficient environmental sensing stimulates studies of new electronic materials. Here, we investigated quasi-one-dimensional titanium trisulfide (TiS3) crystals for possible applications in chemiresistors and on-chip multisensor arrays. TiS3 nanoribbons were placed as a mat over a multielectrode chip to form an array of chemiresistive gas sensors. These sensors were exposed to isopropanol as a model analyte, which was mixed with air at low concentrations of 1–100 ppm that are below the Occupational Safety and Health Administration (OSHA) permissible exposure limit. The tests were performed at room temperature (RT), as well as with heating up to 110 °C, and under an ultraviolet (UV) radiation at λ = 345 nm. We found that the RT/UV conditions result in a n-type chemiresistive response to isopropanol, which seems to be governed by its redox reactions with chemisorbed oxygen species. In contrast, the RT conditions without a UV exposure produced a p-type response that is possibly caused by the enhancement of the electron transport scattering due to the analyte adsorption. By analyzing the vector signal from the entire on-chip multisensor array, we could distinguish isopropanol from benzene, both of which produced similar responses on individual sensors. We found that the heating up to 110 °C reduces both the sensitivity and selectivity of the sensor array.